Present Status and Future Prospects for the Cultivation and Collection of Medicinal Plants of Himachal Pradesh - Gupta, M. P. (Indian Forester, 1988)
An attempt has been made to describe the present state of affairs with respect to the exploitation of medicinal plants in Himachal Pradesh. A case has been made out for standardizing package of practices for the collection, processing, marketing etc. of the important medicinal plants. Suggestions for taking up cultivation in forest areas and popularization of high yielding strains by carrying out genetic study has been made.